Prevalence of Hepatitis C in the Emilia-Romagna Region of Italy: Population-Wide Screening - Gianmarco Imperiali; Matteo Fiore; Alessandro Bianconi; Giovanna Mattei; Giulio Matteo; Giuseppe Diegoli; Esther Rita De Gioia; Cecilia Acuti Martellucci; Maria Elena Flacco; Lamberto Manzoli; Regional HCV Working Group (Viruses)
In agreement with WHO recommendations, the Emilia-Romagna Region, Italy, implemented a population-wide HCV screening program for the treatment of the large asymptomatic infected population. From January 2022, the free-of-charge screening targeted all residents born between 1969 and 1989, prison inmates, and injection drug users. Participants were recruited using phone messages, electronic health record notifications, public advertisement, and direct contact with general practitioners. A single blood sample was collected for anti-HCV IgG testing and, if positive, for reflex HCV–RNA testing. Infected subjects were offered an evidence-based therapeutic pathway. By June 2024, 72.8% of high-risk subjects (n = 19,732), and 36.9% of the general population (n = 488,065) had been screened. A total of 1032 individuals were positive based on the HCV–RNA test, and the detection rate widely differed between the high-risk and the general population (23.8‰ vs. 1.2‰, respectively). Of the infected individuals, 88.1% were seen by a specialist physician, and 74.3% (n = 767) started antiviral therapy. Thanks to multiple recruitment approaches, over one third of the general population participated in HCV screening. The program performance was substantially greater among high-risk individuals compared to the general population. To achieve WHO targets, policymakers might consider expanding the screening to other high-risk subgroups and/or adapting birth cohorts.